Strategi Pemasaran Produk Pembiayaan Hasanah card pada PT Bank Syariah Indonesia Tbk (BSI) KCP Kencong Kabupaten Jember - Nurkholifah husna; Fajriatul Mujtahida; Lilik Munawaroh; Ravika Mutiara Safitrah (Jurnal Ekonomi dan Bisnis Digital, 2023)
Hasanah Card is one of the financing products available at Bank Syariah Indonesia, including BSI KCP Kencong. In its activities to obtain profit sharing from Hasanah Card, it uses mudharabah contracts and musyarakah contracts. However, the people of Kencong are less interested in using Hasanah Card products due to the lack of knowledge of potential customers about Hasanah Card. This research aims to determine what strategies BSI KCP Kencong marketing can use in introducing their product, namely the Hasanah Card. The method used in this research is the brainstorming method by conducting interviews, as well as office observations which have the benefit of finding information, facts that happened, and strategies used in introducing the product. From the results of this research, the marketing strategy used by BSI KCP Kencong is a marketing mix system which is more often referred to as 4P, namely Product, Price, Place and Promotion.